Invasive Traits of Symphyotrichum squamatum and S. ciliatum: Insights from Distribution Modeling, Reproductive Success, and Morpho-Structural Analysis - Alina Georgiana Cîșlariu; Ciprian Claudiu Mânzu; Mioara Dumitrașcu; Daniela Clara Mihai; Marius Nicu Andronache; Petronela Camen-Comănescu; Eugenia Nagodă; Anca Sârbu (Biology)
Understanding the drivers of invasive species’ success is essential for predicting and managing their ecological impacts. Symphyotrichum squamatum, a South American species first recorded in Bucharest in 2015, is currently expanding into urban and peri-urban areas of Romania, raising concerns about its invasive potential. This study provides a comprehensive assessment of its invasiveness by integrating species distribution modeling, a reproductive trait analysis, and morpho-structural evaluations. To deepen our understanding, we compare S. squamatum with S. ciliatum, a species already invasive in Romania, to identify shared traits potentially driving their invasiveness. Using R software (version 4.3.0) with bioclimatic variables, we modeled the potential distribution of both species. The reproductive success of S. squamatum was evaluated through germination tests on seeds from distinct Romanian populations, while anatomical analyses revealed adaptations potentially linked to invasiveness. Our findings indicate that S. squamatum shares traits with successful invaders, as highlighted by its comparison with the invasive S. ciliatum. However, its expansion in Romania appears to be constrained by environmental factors, with continentality emerging as a key determinant influencing the distribution of both species. This study highlights the importance of combining ecological modeling with trait-based analyses to assess invasive potential, offering a robust framework for managing alien species.